2005
DOI: 10.1136/jnnp.2004.036566
|View full text |Cite
|
Sign up to set email alerts
|

EEG coherence reflects regional corpus callosum area in Alzheimer's disease

Abstract: Objective: Correlations between corpus callosum size and interhemispheric EEG coherence were investigated as measures of interhemispheric connectivity in patients with Alzheimer's disease. Methods: 11 patients underwent both magnetic resonance imaging and quantitative electroencephalography to assess corpus callosum size and interhemispheric coherence. For comparison, corpus callosum size was measured in 24 healthy elderly control subjects. Results: Corpus callosum cross sectional area was significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
47
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 14 publications
13
47
1
2
Order By: Relevance
“…A decrease of resting state functional connectivity in Alzheimer's disease patients in the alpha and often also in the beta band has been reported in many EEG and MEG studies (Leuchter et al, 1992;Besthorn et al, 1994;Dunkin et al, 1994;Jelic et al, 1996;Locatelli et al, 1998;Knott et al, 2000;Stevens et al, 2001;Adler et al, 2003;Hogan et al, 2003;Jiang 2005;Koenig et al, 2005;Pogarell et al, 2005). However, a major point of criticism is that such studies were done on the raw EEG and MEG time series.…”
Section: Volume Conductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease of resting state functional connectivity in Alzheimer's disease patients in the alpha and often also in the beta band has been reported in many EEG and MEG studies (Leuchter et al, 1992;Besthorn et al, 1994;Dunkin et al, 1994;Jelic et al, 1996;Locatelli et al, 1998;Knott et al, 2000;Stevens et al, 2001;Adler et al, 2003;Hogan et al, 2003;Jiang 2005;Koenig et al, 2005;Pogarell et al, 2005). However, a major point of criticism is that such studies were done on the raw EEG and MEG time series.…”
Section: Volume Conductionmentioning
confidence: 99%
“…It has even been suggested that Alzheimer's disease can be viewed as a disconnection syndrome (Delbeuck et al, 2003). Support for this concept comes from a number of EEG and magneto-encephalography (MEG) studies using conventional coherence as a measure of functional connectivity (Leuchter et al, 1992;Besthorn et al, 1994;Dunkin et al, 1994;Jelic et al, 1996;Locatelli et al, 1998;Berendse et al, 2000;Knott et al, 2000;Stevens et al, 2001;Adler et al, 2003;Hogan et al, 2003;Jiang 2005;Koenig et al, 2005;Pogarell et al, 2005). In most of these studies a consistent decrease of coherence in the alpha and beta band was reported, whereas results for other bands were more variable.…”
Section: Introductionmentioning
confidence: 99%
“…It seems obvious that loss of anatomical connections between brain areas may lead to a reduction of functional coupling. In AD, atrophy of the corpus callosum has been shown to be associated with loss of lower interhemispheric coherence (Pogarell et al 2005). Furthermore, in multiple sclerosis, associated with widespread degeneration of the white matter, and therefore, loss of anatomical connections, a strong reduction in interhemispheric connectivity has been reported ).…”
Section: Pddmentioning
confidence: 99%
“…Это согласуется со сведения-ми о том, что изменения в α-диапазоне могут отражать сдвиги в состоянии холинергической системы [36][37][38][39][40][41], хотя, по мнению других авторов [65], данный диапазон больше отражает активность дофаминергической систе-мы. Полученные данные мы склонны рассматривать в аспекте связи α-активности преимущественно с состоя-нием холинергической системы.…”
Section: Discussionunclassified
“…В ряде исследований [36][37][38][39][40] было установлено, что изменения ЭЭГ при связанных с нарушением функции холинергической системы заболеваниях преобладают в α-диапазоне в виде снижения мощности и когерентно-сти α-ритма. Представляют интерес также данные F. Lopes da Silva [41] о прямой зависимости между гене-рацией α-ритма и активностью холинергической систе-мы, которая в свою очередь модулируется активностью ствола мозга.…”
unclassified